DO ARTHRITIC PATIENTS TALK MORE? - Rahman, Shafiq; Jan, Bahrawar; Rahman, Khaleeq ur (Journal of Ayub Medical College Abbottabad, 2011)
Background: The modification of speech properties in patients may indicate a more profound pathology. Ample research has been undertaken in relation to different demographic and genetic factors on arthritis but significant research on speech in arthritis had not been conducted globally. The objective of this study was to investigate the effect of arthritis on the duration of speech in patients. Method: It was a randomised control trial conducted at Rehman Medical Institute (RMI), Peshawar, Pakistan between the months of July and August 2010. Two groups of patients were randomised prospectively; 50 arthritic and 50 non-arthritic, seen in an Orthopaedic OPD. Six standard history questions were asked from each patient and the duration of speech was recorded with the help of a stopwatch. A standard Performa was filled for each participant recording his/her personal information, duration of symptoms, time taken to answer the history questions and a brief past history. The Student’s t-test was used to compare the mean durations of speech between arthritic and non-arthritic patients whilst the ANOVA test was applied to compare the mean durations of speech amongst the different forms of arthritis. Pearson’s correlation test and odds ratio were also used to check the association of different quantitative and qualitative variables. Results: A statistically significant correlation was deduced in that arthritic patients talked more than non-arthritic ones (p<0.001). The other factors of age, sex, duration of symptoms and multiplicity of the pain had no influence on the time taken to talk. Conclusion: Arthritic patients speak for a significantly prolonged duration than non-arthritic ones. Keywords: Arthritis, Osteoarthritis, Rheumatoid arthritis, Gouty arthritis, Speech, Pain